2019
DOI: 10.3889/oamjms.2019.238
|View full text |Cite
|
Sign up to set email alerts
|

Angioplasty with Stenting in Acute Coronary Syndromes with Very Low Contrast Volume Using 6F Diagnostic Catheters and Bench Testing of Catheters

Abstract: AIM: To safely perform angioplasties in acute coronary syndromes with low contrast volume using Cordis 6F diagnostic catheters and to perform mechanical bench tests on the diagnostic and guide catheters in a radial path model. METHODS: In 191 patients (242 lesions/268 stents) with acute coronary syndromes angioplasty were performed with cordis 6F diagnostic catheters. RESULTS: The lesions were present at left anterior descending (121), Left main (5), left circumflex (51), ramus (5) and right corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…If unable to differentiate based on these parameters, a fourth investigator (PMik) would select between the papers with the article providing most data regarding our secondary objectives being selected for inclusion. Sixty-seven papers were included in the final statistical analysis4–7 10–72 (figure 1). Efforts to exclude data pertaining to CTO procedures within a larger dataset were made by the authors.…”
Section: Methodsmentioning
confidence: 99%
“…If unable to differentiate based on these parameters, a fourth investigator (PMik) would select between the papers with the article providing most data regarding our secondary objectives being selected for inclusion. Sixty-seven papers were included in the final statistical analysis4–7 10–72 (figure 1). Efforts to exclude data pertaining to CTO procedures within a larger dataset were made by the authors.…”
Section: Methodsmentioning
confidence: 99%
“…However, the force-displacement curve presents better characteristics with 6F diagnostic catheters compared to 5F guide catheters. 17,36 The long-term prognosis after ACS in patients with a mean age of 73 showed that age and creatinine levels were the only indicators of prognosis. Hence, preserving renal function in coronary artery disease patients should be considered a priority.…”
Section: Managing Groin Hematomasmentioning
confidence: 99%